PENGEMBANGAN LKPD ELEKTRONIK DENGAN PENDEKATAN STEM BERBASIS PROJECT-BASED LEARNING MATERI ENERGI DAN PEMANFAATANNYA - Siwi Purwanti; Mona Sholihah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
Currently there is still a need for the development of teaching materials and no electronic LKPD has been found with a project-based STEM approach on energy materials and their utilization. The purpose of this study was to develop and determine the feasibility of electronic LKPD with a PjBL-based STEM approach on energy materials and their utilization. The research method used was RnD research with a development procedure that refered to the ADDIE development model. However, this research was only up to the development stage. The experimental subjects consisted of expert and test subjects, namely learning, material, language, media and teacher experts. The types of data were qualitative and quantitative data. Qualitative data were obtained from the results of expert and teacher reviews in the form of suggestions, input, and comments. Meanwhile, quantitative data were obtained from the scores on the assessment sheet. Data collection instruments used assessment sheets and interviews. The product trial used the developed electronic LKPD and assessment sheet. The results of the development showed that the final score of the learning experts was 86.7 that belonged to the very good category, the material expert got 86.7 in the very good category, the linguist got 91.4 in the very good category, the media expert got 78.9 in the good category, teacher I and teacher II obtained final grades of 97.5 and 88.7, that belonged to the very good categories. If it was calculated as a whole, the final score of 531 was included in the very good category. Therefore, the development of electronic LKPD with a PjBL-based STEM approach on energy materials and their utilization was appropriate to be used as teaching materials in class IV for theme 2 sub-theme 1.